OPTIMIZING THE QUALITY OF CHAR BRIQUETTE PYROLYSIS PRODUCTS OF PLASTIC WASTE - Sunaryo; Sutoyo; Suyitno; Muh. Taufik (Nacreva Publisher, 2023)
Recycling process of the plastic waste into fuel in the concept of Waste to Energy is a technology that began to popularize the pyrolysis method. In addition to liquid fuels as the main product , which is produced from the above method is solid and non - condensable gases. Generaly, the residual gas is burned directly , while the solids can be processed into solid fuel (char briquettes) . To process the solids into a char ( fixed carbon + ash ) then it should be the beginning of a process to remove moisture and reduce levels of volatile matter . Despite a volatile fuel but large levels indicate that the pyrolysis process has not been good , besides the burning application will cause soot . Initial research has resulted in the burning of 8 quality test data sample of 13 samples char briquettes obtained by pyrolysis of polyethylene plastic material with an operating temperature variation between 450-500 ° C , as well as mass variations and types of catalysts Zeolite Y and Natural Zeolite . In addition, the variation was also performed by mixing the PE material with the type of Polystyrene , Polypropylene , Polyethylene Terephthalate , and Other . Char characteristics are known through the proximate test include moisture content , ash , volatile matter and fixed carbon , calorific value is tested through the bomb calorimeter . Combustion quality tested in the furnace at a temperature of 230 ° C ± walls and constant air flow of 0.7 m / s , and the measured emission levels .The problem is in the application note that burning briquettes are not optimized , long heating periods indicated , as well as varying levels of CO . Therefore, it is necessary to the optimization of combustion quality will be analyzed through the ultimate test and the effect of porosity.